Refresentatif Kode Hermeunotik pada Film “1 Kakak 7 Ponakan” (Analisis Studi Semiotika Roland Barthes) - Muhammad Yusuf Yunus; Lilis Suryani; Kurnia Kurnia; Alia Alia (Pepatudzu : Media Pendidikan dan Sosial Kemasyarakatan, 2026)
This study aims to identify the forms of semiotic lexical meaning in the hermeneutic code aspect in Roland Barthes' view, in addition to the use of codes to reveal the meaning in the film, the researcher analyzes the moral message in the film "1 Kakak 7 Ponakan". This study uses a descriptive qualitative approach using documentation techniques, unstructured interviews, and observing and taking notes. The phenomenon in this film instills the value of how boys in a family often have financial burdens in society. Likewise, in this film, it is clearly seen the role of Moko as a boy who becomes the backbone of the family after losing both parents. Therefore, in this study, the representative of the analysis will be the role of a boy named Moko. At the ideological level, Moko's character represents hegemonic clarity combined with empathy and concern, indicating a cultural shift that men are not only seen as breadwinners, but also emotional caregivers. The conclusion of this study confirms that the film 1 Kakak 7 Ponakan represents boys as central figures who bear cross-generational responsibilities while simultaneously revealing ideological messages about sacrifice, responsibility, and the transformation of the role of masculinity in Indonesian culture.